2020
DOI: 10.1038/s41467-019-14043-y
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil microvesicles drive atherosclerosis by delivering miR-155 to atheroprone endothelium

Abstract: Neutrophils are implicated in the pathogenesis of atherosclerosis but are seldom detected in atherosclerotic plaques. We investigated whether neutrophil-derived microvesicles may influence arterial pathophysiology. Here we report that levels of circulating neutrophil microvesicles are enhanced by exposure to a high fat diet, a known risk factor for atherosclerosis. Neutrophil microvesicles accumulate at disease-prone regions of arteries exposed to disturbed flow patterns, and promote vascular inflammation and … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
110
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 111 publications
(114 citation statements)
references
References 63 publications
(69 reference statements)
3
110
1
Order By: Relevance
“…Cellular senescence for example contributes to agedependent changes in circulating extracellular vesicle cargo 46 . Moreover, the differential loading of vesicles is correlated to different human diseases [47][48][49] . Likewise, for the cellular part, resolution can be increased.…”
Section: Discussionmentioning
confidence: 99%
“…Cellular senescence for example contributes to agedependent changes in circulating extracellular vesicle cargo 46 . Moreover, the differential loading of vesicles is correlated to different human diseases [47][48][49] . Likewise, for the cellular part, resolution can be increased.…”
Section: Discussionmentioning
confidence: 99%
“…This indicated that miR-155 promoted and Bmal1 hindered the progression of atherosclerosis. According to Gomez et al, exosomes carrying miR-155 released from neutrophils during vascular infiltration were fused with ECs, leading to vascular inflammation and atherosclerosis (24). Faccini et al also indicated the high diagnostic value of miR-155 in coronary atherosclerosis (25).…”
Section: Discussionmentioning
confidence: 99%
“…Reduced neutrophil migratory accuracy and reduced bacterial killing has been identified in hyperglycaemia and replicated in vitro following neutrophil exposure to serum from diabetic patients [78]. In vitro, neutrophils have also been implicated in cell-to-cell crosstalk, with neutrophil microvesicles associated with inducing classical pathological changes in diabetic cardiovascular pathology [79] and COPD [80]. Furthermore, age-related changes seen in the muscle (e.g.…”
Section: Theme 1: Accelerated Ageing In Multimorbiditymentioning
confidence: 97%